Epidemiological Evidence for Fecal-Oral Transmission of Murine Kobuvirus - Gao, Yuhan; He, Wenqiao; Fu, Jiaqi; Li, Yongzhi; He, Huan; Chen, Qing (Frontiers in Public Health, 2022)
Background: Murine Kobuvirus (MuKV) is a novel picornavirus of the genus Kobuvirus, and was first identified in the feces of murine rodents in the USA in 2011. There is limited information on the transmission route of MuKV. Thus, we conducted a study to investigate virus detection rates in fecal, serum, throat, and lung tissue samples from murine rodents. Results: A total of 413 fecal samples, 385 lung samples, 269 throat swab samples, and 183 serum samples were collected from 413 murine rodents (Rattus norvegicus, Rattus tanezumi, and Rattus rattus) captured in urban Shenzhen. Kobuviruses were detected via RT-PCR. Only fecal samples were positive, with prevalence rates of 34.9% in Rattus norvegicus and 29.4% in Rattus tanezumi. Phylogenetic analysis based on partial 3D and complete VP1 sequence regions indicated that all of the MuKV sequences obtained belonged to Aichivirus A, and were genetically closely related to other MuKVs reported in China, Hungary, and the USA. Twenty-eight full-length MuKV sequences were acquired. Phylogenetic analysis of two sequences randomly selected from the two species (SZ59 and SZ171) indicated that they shared very high nucleotide and amino acid identity with one another (94.0% and 99.3%, respectively), and comparison with human Kobuvirus revealed amino acid identity values of approximately 80%. Additionally, a sewage-derived sequence shared high similarity with the rat-derived sequences identified in this study, with respective nucleotide and amino acid identity values from 86.5% and 90.7% to 87.2% and 91.1%. Conclusion: The results of the current study provide evidence that murine Kobuvirus is transmitted via the fecal-oral route.